Kualitas Pelayanan Publik dalam Bidang Administrasi Kependudukan di Kecamatan Pagedangan di Tinjau dari Undang-undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik - Fikri Jamal; Bima Guntara (Program Studi Hukum Universitas Pamulang, 2020)
It is the obligation of the Government as a public service provider to be responsible and continue to provide the best service for the sake of improving quality public services. Community satisfaction is a measure of the success of public services provided by public service providers. Today quality is an important topic in service delivery, including in government organizations or institutions as public service providers. Quality is a dynamic condition that affects products, services, people, processes and the environment that meet or exceed expectations. Service Quality is all forms of activities undertaken to meet consumer expectations. Service in this case is defined as a service provided in the form of convenience, speed, relationship, ability and hospitality addressed through attitudes and characteristics in providing services for satisfaction. This research is a descriptive study using a qualitative approach to determine the quality of public services in the field of population administration in Pagedangan District. The data collection technique is done by using observation, interview, and documentation techniques. The data analysis technique used is an interactive model. It is expected that the results of this study can be described; (1) Quality of public services in the field of population administration in Pagedangan District. (2) Obstacles to public services in the field of population administration at the Pagedangan District level. (3) efforts to improve public services in the field of population administration at the Pagedangan District level.